THE EXISTENCE OF REGIONAL REPRESENTATIVE COUNCIL IN THE POSITION OF THE LEADERS OF THE PEOPLE'S CONSULTATIVE ASSEMBLY - Rahmat Bijak Setiawan Sapii; Yoan Dwi Pratama; Tasya Darosyifa; Ali Imran Nasution (Jurnal Cendekia Hukum, 2022)
Through the fourth amendment to the 1945 Constitution of the Republic of Indonesia, the Regional Representative Council was formed as a representation of groups and regions which also added new rooms in parliament. The existence of the DPD is often considered weak because of its limited authority both in carrying out functions and getting attention in filling the MPR leadership positions which are dominated by the DPR in the 2019 MD3 Law. The purpose of this study is to determine, examine and analyze the existence of the Regional Representatives Council in occupying the leadership position of the People's Consultative Assembly and examine the compositional division that should be between the DPR and DPD in occupying the leadership position of the People's Consultative Assembly. This research method uses normative law with a statutory and conceptual approach. This research concludes that the composition of leadership position between DPR and DPD to fill the MPR is not balanced.  Because if you stick to the 2019 MD3 Law, it will cause injustice to the DPD which is a high state institution at the level of the DPR. In addition, there is also legal uncertainty regarding the number of MPR leaders who come from representatives of the DPR as a consequence of implementing the parliamentary threshold. Therefore, we need an ideal arrangement that does not come out of the constitution but provides legal certainty and justice.